2015
DOI: 10.1155/2015/895416
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Th9 Cell Related Cytokine and Transcription Factors in Patients with Hepatic Alveolar Echinococcosis

Abstract: Human alveolar echinococcosis (AE) is a lethal parasitic infectious disease which may lead to liver failure if left untreated. It is caused by the larval stage of the fox tapeworm Echinococcus multilocularis and usually develops a substantial infiltrative occupation in solid organs. During the infection, T helper subsets are known to play crucial role in crosstalk between the parasite and human host. Th9 cells, a new member of CD4+ T cell family which is characterized by its specific cytokine IL-9 and transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…It also serves to stabilize and expand Th17 cell functions and to enhance the expression of IL-17 in granulomatous lesions 27 , 28 . The immunopathological consequences of increased IL-17 production have been shown in both human and experimental AE 10 , 11 . Besides, elevated Th17 cell response might increase angiogenesis and inflammation that provides a new environment and nutrition to the parasite while accelerating disease progression 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also serves to stabilize and expand Th17 cell functions and to enhance the expression of IL-17 in granulomatous lesions 27 , 28 . The immunopathological consequences of increased IL-17 production have been shown in both human and experimental AE 10 , 11 . Besides, elevated Th17 cell response might increase angiogenesis and inflammation that provides a new environment and nutrition to the parasite while accelerating disease progression 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence supports that increased FDG uptake measured by PET in patients with progressing AE is based on the periparasitic cell infiltration and thus reflects the cross-talk between the parasite and human host’s immune cells 9 . Several studies have focused on this cross-talk and the possible role of dendritic cells, T helper (Th) cells and the cytokines they produce both in humans and experimental models 10 , 11 . They have usually separately addressed peripheral or regional immune response; in addition, comparison between progression, stability or regression of lesions, whenever studied, was assessed on clinical grounds only 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been recently shown that IL‐9 and IL‐4 were rarely produced by the same T cell, indicating that Th9 cells form a unique Th cell subset . The critical roles of IL‐9 in a broad range of autoimmune disorders, allergic inflammation and cancers, as well as parasitic infection, has aroused interest . However, studies on the relationship between IL‐9 and schistosomiasis are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…23 The critical roles of IL-9 in a broad range of autoimmune disorders, allergic inflammation and cancers, as well as parasitic infection, has aroused interest. [24][25][26][27][28][29][30] However, studies on the relationship between IL-9 and schistosomiasis are scarce. Our previous study investigated the dynamic changes of Th9/IL-9 in S. japonicum-infected mice and found that egg granulomas developed synchronously with the expression changes of IL-9 and PU.1 in liver.…”
Section: Introductionmentioning
confidence: 99%
“…Tuxun et al [10] IL-10 and TGF-β levels are high in the course of AEprogression in humans. Gottstein et al [20] IL-12, IL-23, IL-17A, IL-17F, and IL-10 levels were higher in patients with hepatic AE.…”
Section: Resultsmentioning
confidence: 99%